The Informal City as Urban Idealisation - Carlos Almeida Marques (Buildings)
The informal city, also known as the clandestine city and usually associated with the phenomenon of urban self-organisation, is a reality that cuts across all societies today and occurs in the most diverse regions of the globe, which raises the following question: Why do such different cultures, in such different geographies, adopt a common idea of an ‘informal city’ to live in? Despite the dramatic human condition that characterises slums and informal settlements, it is challenging to understand how these settlements can be adopted as a living space for so many and such diverse populations, admitting the interpretation that it is a utopia and an urban idealisation. Informal urbanisation processes occur outside the system and on the fringes of the practice of ‘institutional urban planning’, as a necessary and immediate response to the absence of public land policies, housing market failures or situations arising from social and economic crises. The object of this study is to find out to what extent the configuration of space, the territorialisation model and the morphology of the informal city, characterised by an entropic urbanism, correspond to an urban organisational structure that occurs when it is up to society to provide its own habitat and urban environment.